Substitute and Add-on Devices Used in Inhalation Therapy: is it Safe to Recommend Replacing the Ventolin™ Actuator with the Sports-Haler™ - Bosnic-Anticevich, Sinthia; Mavritsakis, Sophia; Hoe, Susan; M. Young, Paul; Traini, Daniela (Drug Delivery Letters, 2016)
Pressurised metered dose inhalers (pMDI) are still the most heavily prescribed medicines for the treatment of asthma. Various add-on devices are made available through pharmacies either on prescription, over-the-counter or off-theshelf. These include actuation aids, spacers and alternative actuators. The Sports- Haler™ is a replacement actuator for the conventional Ventolin™ actuator and offers a compact and colourful alternative to the conventional design. This article evaluates the performance of this replacement device and compares it to the standard product using Pharmacopeia methodology. In general, there were no differences in the aerosol performance and thus projected lung deposition of salbutamol sulphate. We discuss the pros and cons of such add-on devices from a pharmacy perspective and highlight potential issues that may be encountered when patients choose to modify the standard regulated pharmaceutical product. There are several considerations, which need to be reviewed when making decisions about the use of substitute and/or add-on devices.
Keywords: inhalation add-on devices